Strategi Pengembangan Daya Tarik Wisata dalam Meningkatkan Kunjungan Wisatawan di Curug Aseupan Parongpong - Apay Safari; Anti Riyanti (STIEPAR YAPARI Bandung, 2023)
This study aims to find out the tourist attraction of the Aseupan Parongpong Waterfall. Be a travel recommendation by improving what infrastructure is needed, increasing visits and knowing the positive and negative impacts of tourism development of Aseupan Parongpong Waterfall. This study uses descriptive qualitative methods where this research is carried out naturally with natural results according to what was obtained at the time of the research. Data collection techniques were carried out by observation, documentation, and interviews and then validated by triangulation. After validation, it is reprocessed with a SWOT analysis where this analysis aims to determine the intended target market. From the results of the research, the attractiveness of the Aseupan Parongpong waterfall is in a good category because tourists who visit want a beautiful natural atmosphere but for the satisfaction of tourists it is necessary to improve infrastructure and opening access roads to other waterfalls in the location so that it adds to the attraction. Other attractions are being worked on by the Pokdarwis to hold cultural performances around the location, so the attraction of Aseupan Parongpong Waterfall can be categorized as superior for increasing tourist visits. The development strategy that will be carried out by the manager is quite good which will improve the footpath infrastructure first, then the manager is proposing additional employees to maximize existing facilities so that the cleanliness of the location is more considered.